Topical corticosteroids in the treatment of acute sunburn: a systematic review (Journal of Ideas in Health, 2024)
Background: Acute sunburn is a prevalent dermatological issue, particularly affecting individuals with fair skin types I-III. It is characterized by erythema, edema, and discomfort due to ultraviolet (UV) radiation exposure. Topical corticosteroids are commonly used for their anti-inflammatory properties, but their efficacy in sunburn treatment is debated due to limited high-quality evidence from randomized controlled trials (RCTs). This study aims to assess the efficacy of topical corticosteroids in relieving symptoms and inflammation of sunburn. Methods: A systematic review was conducted by searching PubMed, Web of Science, ProQuest, Scopus, and Cochrane Central Register of Controlled Trials (CENTRAL) for studies published up to April 30, 2024. Keywords included combinations of terms related to corticosteroids, topical application, and sunburn. Studies were selected based on PRISMA 2020 guidelines, focusing on adult patients treated with topical corticosteroids compared to placebo. Data extraction and quality assessment were independently performed by two researchers using the Cochrane Collaboration’s Risk of Bias tool.Results: The review included six RCTs with a total of 339 participants, aged 18-68 years, conducted in Europe and the USA. Various topical corticosteroids were studied, including methylprednisolone aceponate, hydrocortisone 17-butyrate, and hydrocortisone-21-acetate. Treatment durations ranged from single applications to twice daily for seven days. The results demonstrated that prolonged treatment with topical corticosteroids significantly reduced sunburn symptoms such as erythema and pain. When applied for seven days, treated areas showed lower sunburn reaction scores and reduced inflammation compared to untreated areas. Early application of corticosteroids, particularly within 6 hours post-exposure, was more effective than later applications. Histological analyses supported these findings, showing improvements in epidermal thickness and reduced dermal inflammation in treated areas.Conclusion: Topical corticosteroids can effectively alleviate acute sunburn symptoms and aid skin recovery by targeting inflammatory pathways. Their efficacy is enhanced with prolonged and early application. Further research is needed to optimize treatment protocols and assess long-term effects to fully realize the therapeutic potential of corticosteroid therapy in managing acute sunburn.
Keywords: Efficacy, Sunburn, Systematic Review, Topical Corticosteroids, Indonesia